2014
DOI: 10.5792/ksrr.2014.26.4.236
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Intra-Articular Injection of Thrombin-Based Hemostatic Agent in the Control of Bleeding after Primary Total Knee Arthroplasty

Abstract: PurposeTo evaluate the hemostatic effect of intraarticular injection of a thrombin-based hemostatic agent in total knee arthroplasty (TKA).Materials and MethodsWe performed a prospective randomized controlled trial on the use of a thrombin-based hemostatic agent in patients undergoing unilateral TKA. A total of 100 TKA patients were enrolled, with 50 patients randomized into the study group and the other 50 patients into the controlled group. Drain output, hemoglobin level, total red blood cell loss for 24 hou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(31 citation statements)
references
References 15 publications
1
30
0
Order By: Relevance
“…No additional studies were obtained after the reference review. Finally, four independent RCTs 11,13,15,16 were eligible for data extraction and meta-analysis, as indicated by the flowchart in ►Fig. 1.…”
Section: Literature Searchmentioning
confidence: 99%
See 4 more Smart Citations
“…No additional studies were obtained after the reference review. Finally, four independent RCTs 11,13,15,16 were eligible for data extraction and meta-analysis, as indicated by the flowchart in ►Fig. 1.…”
Section: Literature Searchmentioning
confidence: 99%
“…In each study, Floseal was administered intra-articularly before suturing, though the dosages varied (5-10 mL). Three studies 11,13,16 reported a transfusion trigger. Cemented prostheses were reported in three studies, 11,15,16 while the remaining study incorporated uncemented prostheses.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations